Use of Left Ventricular Assist Device (HeartMate II): A Singapore Experience. Issue 7 (7th January 2014) - Lim, Choon Pin; Sivathasan, Cumaraswamy; Tan, Teing Ee; Lim, Chong Hee; Kerk, Ka Lee; Sim, David Kheng Leng
Abstract Recent advances in medical and device therapies in heart failure have improved the survival of patients with heart failure. However, due to the limited availability of suitable heart donors, left ventricular assist devices (LVADs) have become an important tool as a bridge‐to‐heart transplantation for patients with refractory heart failure in Singapore. We report our experience with the HeartMate II (HMII) LVAD (Thoratec Corporation, Pleasanton, CA, USA) as a bridge‐to‐heart transplant in our center from 2009 to 2012. This was a retrospective review of 23 consecutive patients who underwent HMII LVAD implantation in our center between May 2009 and December 2012. All patients were classified as Interagency Registry for Mechanically Assisted Circulatory Support (INTERMACS) levels 1 to 3 and underwent LVAD implantation as a bridge‐to‐heart transplant. There were 17 male and 6 female patients. The mean age was 43.6 years old (range 14 to 64). The etiologies of heart failure included ischemic heart disease [8], idiopathic dilated cardiomyopathy [11], viral myocarditis [2], and chemotherapy‐induced cardiomyopathy [2]. Nine patients were INTERMACS level 1, 12 patients level 2, and two patients level 3. All patients successfully underwent HMII LVAD implantation. There was no mortality within the first 30 postoperative days. Postoperative complications included stroke with full neurological recovery (21.7%), mediastinal infection (21.7%), cardiac tamponade or mediastinal collection requiring reopening of the chest (39.1%), cardiac arrhythmia (13.0%), and pump thrombosis with pump replacement (4.3%). All patients were discharged from hospital after LVAD implantation. Three patients experienced driveline infections during outpatient follow‐up. There were 19 readmissions due to the following conditions: sub‐therapeutic anticoagulation (13.0%), gastrointestinal bleeding (13.0%), suspected pump thrombosis (13.0%), transient ischemic attack (8.7%), arrhythmia (8.7%), congestive cardiac failure due to severe aortic regurgitation (8.7%), right ventricular failure (4.3%), rhabdomyolysis (4.3%), and hematuria (4.3%). Post‐LVAD implantation, 20 patients were functionally New York Heart Association (NYHA) class I, while 3 reported NYHA III symptoms. Three patients were successfully bridged to heart transplantation. One patient was successfully explanted 11 months after LVAD implantation. There were two mortalities during the follow‐up period. The average duration of LVAD support was 522 days (range 47 to 1316 days). The HeartMate II LVAD has proven to be effective in our Asian population. Driveline infection rate remains low even in the tropical hot, humid climate in Singapore. With more patients ending up on extended periods of LVAD support, increased emphasis in the detection and management of long‐term complications of ventricular assist devices will be needed.